2013
DOI: 10.1080/13632469.2013.801377
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic P-Y Curves for Dry Sand from Centrifuge Tests

Abstract: In this article, the simplified dynamic p-y backbone curve was suggested through a series of dynamic centrifuge tests. The centrifuge tests were carried out for a single pile in dry sand, while changing the conditions such as pile diameters, relative densities, input acceleration amplitudes and frequencies. Based on the results, the dynamic p-y backbone curve was formed as a hyperbolic function by connecting the peak points of the resulting experimental dynamic p-y curves, which corresponded to the maximum soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…The API [8] method is one of the most widely used methods for the seafloor, but there are many studies which report that it overestimates the initial modulus of subgrade reaction for piles of a larger caliber [13,30,34]. In addition, Yoo et al [15] reported test results that were up to 80% smaller than the API [8] modulus of subgrade reaction. The suggested cyclic p-y curve is based on the soil properties and pile diameter.…”
Section: Suggested Cyclic P-y Curvementioning
confidence: 99%
See 1 more Smart Citation
“…The API [8] method is one of the most widely used methods for the seafloor, but there are many studies which report that it overestimates the initial modulus of subgrade reaction for piles of a larger caliber [13,30,34]. In addition, Yoo et al [15] reported test results that were up to 80% smaller than the API [8] modulus of subgrade reaction. The suggested cyclic p-y curve is based on the soil properties and pile diameter.…”
Section: Suggested Cyclic P-y Curvementioning
confidence: 99%
“…Li et al [14] used centrifuge model tests to analyze the effect of secant stiffness on cyclic lateral load. Yoo et al [15] used a model aluminum pile in centrifuge model tests in dry sand to compare the static p-y curve with the API static p-y curve, and they proposed a dynamic p-y curve. However, the dynamic p-y curve was found for an earthquake load, caused by a vibrating table.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the reliability and minimize the error of the proposed numerical model, a validation procedure was carried out by comparing the dynamic pile internal responses calculated by the numerical model with those measured by the dynamic centrifuge model tests (Yoo et al, 2013) [20]. The centrifuge model tests were performed with the KAIST dynamic centrifuge facility in Korea, which has a 5 m radius, 2.5 ton payload and a up to 100 g centrifugal acceleration.…”
Section: Validation Of Proposed Modelmentioning
confidence: 99%
“…[19]. Validation of the proposed numerical model was carried out comparing internal pile responses of two model pile cases obtained from centrifuge tests and numerical simulation after modeling the dynamic centrifuge test performed by Yoo et al (2013) [20] using the proposed numerical model. Thereafter, the dynamic behavior of pile was thoroughly investigated by performing a parametric study using a verified numerical model.…”
Section: Introductionmentioning
confidence: 99%
“…Because most approaches assume a condition in which a cyclic or static load to is applied to the pile head, they are able to explain the nonlinear relationship between the pile displacement and the ground. However, because the stiffness of soil decreases as the amplitude of the load increases, and because there are cases in which the inertia or attenuation of the ground that occurs under dynamic loading cannot be evaluated [9], dynamic loads such as earthquake loads cannot be reasonably considered in seismic design [10][11][12]. To address this issue, studies attempting to develop a dynamic p-y curve for piles are currently underway.…”
Section: Introductionmentioning
confidence: 99%